2014
DOI: 10.2475/08.2014.01
|View full text |Cite
|
Sign up to set email alerts
|

Aridification of Central Asia and uplift of the Altai and Hangay Mountains, Mongolia: Stable isotope evidence

Abstract: Central Asia has become increasingly arid during the Cenozoic, though the mechanisms behind this aridification remain unresolved. Much attention has focused on the influence and uplift history of the Tibetan Plateau. However, the role of ranges linked to India-Asia convergence but well north of the Plateau-including the Altai, Sayan, and Hangay-in creating the arid climate of Central Asia is poorly understood. Today, these ranges create a prominent rain shadow, effectively separating the boreal forest to the n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
66
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(67 citation statements)
references
References 101 publications
0
66
1
Order By: Relevance
“…HYSPLIT has been used to demonstrate the origin of moisture-bearing air parcels to explain both modern and sedimentary δ 18 O data (e.g., Bershaw et al, 2012;Breitenbach et al, 2010;Caves et al, 2014;Feng et al, 2014;Oster et al, 2012;Sjostrom and Welker, 2009). We focus specifically on two sites that span the latitudinal breadth of Central Asia: western Mongolia (western Valley of Lakes; 47.14N 93.06E) in northern Central Asia and the Qaidam Basin (37.3N 96.7E) on the northern edge of the Tibetan Plateau.…”
Section: Hysplit Modelingmentioning
confidence: 99%
“…HYSPLIT has been used to demonstrate the origin of moisture-bearing air parcels to explain both modern and sedimentary δ 18 O data (e.g., Bershaw et al, 2012;Breitenbach et al, 2010;Caves et al, 2014;Feng et al, 2014;Oster et al, 2012;Sjostrom and Welker, 2009). We focus specifically on two sites that span the latitudinal breadth of Central Asia: western Mongolia (western Valley of Lakes; 47.14N 93.06E) in northern Central Asia and the Qaidam Basin (37.3N 96.7E) on the northern edge of the Tibetan Plateau.…”
Section: Hysplit Modelingmentioning
confidence: 99%
“…A comparable climate-sensitivity is documented for δ 13 C values in soil carbonates. Carbon isotopes in the Eocene to Upper Miocene section of the Valley of Lakes have been studied by Caves et al 11 , who identified two main mechanisms to explain the observed increase in δ 13 C in paleosol carbonates. These are a decrease in primary productivity due to increasing aridity and an increase in evaporation coupled with lowered precipitation.…”
Section: Resultsmentioning
confidence: 99%
“…Between 34 and 32 Ma (biozone A) δ 26 . Intensified uplift of the Tibetan plateau and the Hangay Mountains, as well as, and the prevailing westerlies which carry low moisture, amplified aridity 10,11,30 . Based on sedimentological evidence, the depositional environments in the Taatsiin Gol Basin is interpreted as semiarid open steppe with ephemeral rivers and playa lakes 7 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering its present day distribution (Fig. 15), the differentiation of the subgenus Phryganocleonus may have been triggered by the uplift of the Asian mountain chains, with subsequent habitat aridification, that occurred in the late Miocene (Caves et al, 2014). These species are nowadays adapted to the montane xerophytic habitat and appear to have a relict, very limited areal, probably determined by isolation and speciation by vicariance.…”
Section: Distribution and Ecologymentioning
confidence: 99%